The Rate of Posterior Labral Extension In Operatively Treated Bankart Lesions. Issue 7 (29th July 2019) - Golan, Elan J.; Li, Ryan Tianran; Vaswani, Ravi Surender; Lesniak, Bryson P.; Lin, Albert
Objectives: Traumatic avulsion of the antero-inferior glenoid labrum is a well-recognized sequela of shoulder dislocation. Such Bankart lesions are readily identified on pre-operative imaging, and results of arthroscopic management of these lesion are favorable. However, the frequency with which such antero-inferior lesions propagate posteriorly remains unclear. Further, how well pre-operative imaging detects posterior labral extension remains unknown. The purpose of this study was to investigate both the rate of posterior extension in operatively managed Bankart lesions and the ability of MRI to identify such lesions prior to surgery. Methods: A retrospective review was conducted of patients undergoing operative management for a diagnosis of Bankart Lesion. All patients had a history of traumatic anterior shoulder dislocation. Patients with a history of known concomitant pathology in the ipsilateral shoulder, multi-directional instability, or prior shoulder surgery were excluded. All patients underwent a pre-operative arthrogram which was read by a trained MSK radiologist and reviewed by an orthopedic practitioner assessing for involvement of the posterior labrum. Operative dictations were then reviewed as a gold standard for posterior labral involvement. Follow up data was also reviewed to determine if posterior extension was a risk factor for post-surgical failure. Calculated rates of posterior involvement, as well as the ability of MRI arthrogram to detect posterior labral pathology were analyzed and compared via chi-squared tests. Results: Review yielded 95 shoulders with arthroscopy confirming an antero-inferior labral avulsion. Of these, 20% (19 shoulders) demonstrated involvement of the posterior labrum during arthroscopy. MRI arthrogram findings were equivalent to the arthroscopic findings 82.1% (78/95) of the time when read by a radiologist as compared to 91.6% (87/95) of the time when reviewed by a sports-trained orthopedist (p= .053). Posterior extension was detected in 8/19 (42.1%) of cases when the arthrogram was read by a radiologist alone compared to 16/19 (84.2%) of cases when the arthrogram as read by a sports-trained orthopedist (p= .007). There was no association between Bankart lesions with demonstrated posterior extension and those repairs that eventually went on to failure (p = .29). Conclusion: Propagation of a Bankart lesion into the posterior labrum is relatively common following shoulder dislocation, with data from this review demonstrating a rate of 20%. Based on our findings, careful assessment of the posterior labrum on MRI arthrogram may reveal the majority, but not all, of these lesions prior to surgery. Practitioners should maintain a high level of suspicion for posterior labral involvement, both for pre-operative planning and during operative management of traumatic shoulder dislocations.